KARAKTERISTIK PERTUMBUHAN REMAJA BERDASARKAN EKOSISTEM WILAYAH DI PROVINSI JAWA BARAT - Yudhistira Prasasta; Hidayat Syarief; Yayuk Farida Baliwati (Food and Nutrition Society of Indonesia, 2012)
The study aimed to analyze growth characteristic of adolescents using height-for-age (HAZ) and BMI-for-age (BAZ) z scores based on regional ecosystem in West Java Province namely coastal area (Cirebon), mountainous area (Bandung), and mixture between coastal and mountainous area (Garut). The design of the study was cross sectional study using secondary data from Riskesdas 2007. Total number of adolescents was 1,674 subjects. The growth characteristics of adolescents in Garut District based on HAZ was correlated with occupation of the head family (p=0.001; r=-0.145), while based on BAZ it was correlated with per capita protein intake (p=0.028; r=-0.093). Adolescents in Bandung District based on HAZ index correlated with education of the head family (p=0.040; r=0.081), occupation of the head family (p=0.003; r=-0.118), per capita energy intake (p=0.031; r=-0.085), and per capita protein intake (p=0.002; r=-0.124), while the BAZ correlated with education of the head of the family (p=0.017; r=0.095). Growth characteristics of adolescents in Cirebon District for HAZ was correlated with per capita energy intake (p=0.044; r=-0.086), while BAZ was correlated with education of the head family (p=0.016; r=0.102).Keywords: